Competition for molecular oxygen and electron donor between phenol and quinoline during their simultaneous biodegradation. (July 2018) - Zou, Shasha; Zhang, Bingbing; Yan, Ning; Zhang, Chenyuan; Xu, Hua; Zhang, Yongming; Rittmann, Bruce E.
Graphical abstract: Highlights: Phenol and quinoline biodegradations begin with mono-oxygenations that require O2 and 2H. Inhibition occurred between phenol and quinoline due to competition for O2 and 2H. Adding electron donor could relieve inhibition if the oxygen concentration was high. Adding electron donor could not relieve inhibition if DO was significantly limiting. Substrates-removal rates were proportional to electron donor available based on equivalents. Abstract: It is common that phenol and quinoline co-exist in the same industrial wastewater, such as coking wastewater. For both biodegradations, the initial steps are mono-oxygenation reactions, which require two co-substrates: molecular oxygen (O2 ) and an intercellular electron donor (2H). Competition for O2 and 2H was investigated using a vertical baffled bioreactor (VBBR) with a biofilm acclimated to phenol and quinoline biodegradation. Batch experiments documented mutual inhibition between phenol and quinoline, which competed for O2, 2H, or both during simultaneous biodegradation. Low DO was a limiting factor for phenol and quinoline biodegradations, as both rates slowed significantly for DO ≤ 3 mg/L, compared to DO ≥ 5 mg/L. A DO concentration of 0.5 mg/L led to 89% and 65% slower removal kinetics for phenol and quinoline, respectively. Although adding succinate as an exogenous electron donor was able to alleviate competition when the DO was 4 ∼ 5 mg/L, it had no benefit for a DO ≤ 3 mg/L. Thus, significant DO limitation could not be overcome by addition of more donor. The results imply that a strategy that involves adding or creating an exogenous electron donor may be effective only when DO is not significantly rate limiting for the initial oxygenation reactions.